Isolation and Identification of Enteroviruses from Sewage and Sewage-Contaminated Water Samples from Ibadan, Nigeria, 2012-2013 (2017)
In 2010, we described sewage contaminated water (SCW) bodies that consistently yielded enteroviruses (EVs) in enterovirus surveillance (ES) sites in Lagos, Nigeria. By 2012, we demonstrated the presence and circulation of Wild Poliovirus 3 (WPV3) in these ES sites. Here we describe ES sites that consistently yield EVs in Ibadan metropolis southwest Nigeria. Twenty-five ES samples were collected by grab method from nine sites between October, 2012 and March, 2013. Samples were concentrated and four (RD, HEp2C, MCF-7 and L20B) different cell lines used for virus isolation from the concentrates. Isolates were subjected to RNA extraction, cDNA synthesis, PanEnterovirus 5l-UTR and VP1 assays. Unidentifiable isolates were further subjected to species-specific RTPCR assays. Amplicons were sequenced, isolates identified and subjected to phylogenetic analysis. Twenty-five isolates were recovered from 8 (32%) of the samples collected. Twenty-three of the isolates were identified as EVs by the PanEntero5l-UTR assay. Thirteen (57%) of the 23 EVs were positive for the VP1 assay, and identified as Coxsackievirus B3 (CVB3) (1 isolate), CVB6 (1 isolate), E6 (2 isolates), E7 (5 isolates), E11 (1 isolate), E12 (1 isolate) and E13 (2 isolates). None and 2 (25%) of the remaining isolates were positive for the EV-B and EV-C assays, respectively. The 2 EV-C positive enteroviruses were isolated on MCF-7. This study describes three very productive ES sites, and documents the presence of CVB3, CVB6, E6, E7, E11, E12 and, E13 in Ibadan, Nigeria. Including other cell lines in EV isolation protocols can broaden the diversity of EV types recoverable.